Diagnostic accuracy of disorganization of the retinal inner layers in detecting macular capillary non‐perfusion in diabetic retinopathy. (24th June 2015) - Nicholson, Luke; Ramu, Jayashree; Triantafyllopoulou, Ioanna; Patrao, Namritha V; Comyn, Oliver; Hykin, Philip; Sivaprasad, Sobha
Abstract: Background: Disorganization of the retinal inner layers (DRIL) on optical coherence tomography (OCT) is thought to represent retinal capillary non‐perfusion (CNP) in eyes with diabetic retinopathy. This study was designed to evaluate the ability of DRIL to accurately predict CNP. Design: Retrospective masked reliability and diagnostic accuracy study performed in the National Institute for Health Research (NIHR) Moorfields Biomedical Research Centre, London, UK Samples: Retinal images of patients with diabetic retinopathy Methods: The OCT images from 90 separate areas of angiographically confirmed perfused and non‐perfused areas of the macula from 37 eyes of 31 patients were anonymized and coded. Two masked graders independently graded these OCT scans for the presence or absence of DRIL to determine the intergrader reliability. The diagnostic accuracy of DRIL in identifying CNP was evaluated from the results obtained. Main Outcome Measures: Sensitivity and specificity of DRIL in accurately detecting CNP Results: The intergrader agreement was high with a Cohen's kappa of 0.909. DRIL was present in 84.4% (38/45) of non‐perfused retina and none in perfused retina (0/45). The sensitivity and specificity of DRIL in detecting angiographic evidence of CNP was 84.4% and 100%, respectively. The positive predictive value was 100% and the negative predictive value was 86.5%. Conclusions: The presence of DRIL is a reliable predictor of areas of macular CNP. However, DRIL is not a universal finding of non‐perfusion, with some cases exhibiting absence of DRIL despite angiographic CNP.